2008
DOI: 10.1016/j.cognition.2007.12.012
|View full text |Cite
|
Sign up to set email alerts
|

Give and take: Syntactic priming during spoken language comprehension

Abstract: Syntactic priming during language production is pervasive and well-studied. Hearing, reading, speaking or writing a sentence with a given structure increases the probability of subsequently producing the same structure, regardless of whether the prime and target share lexical content. In contrast, syntactic priming during comprehension has proven more elusive, fueling claims that comprehension is less dependent on general syntactic representations and more dependent on lexical knowledge. In three experiments w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

26
213
8

Year Published

2013
2013
2021
2021

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 148 publications
(247 citation statements)
references
References 28 publications
26
213
8
Order By: Relevance
“…Bock, 1986;Bock & Loebell, 1990) or in faster speech onsets for repeated syntactic structures (Corley & Scheepers, 2002;Segaert, Menenti, Weber, & Hagoort, 2011;Smith & Wheeldon, 2001;Wheeldon & Smith, 2003;Wheeldon, Smith, & Apperly, 2011). Syntactic priming in comprehension is shown in anticipatory eye-movements to pictures (Arai, van Gompel, & Scheepers, 2007;Carminati, van Gompel, Scheepers, & Arai, 2008;Thothathiri & Snedeker, 2008a;Traxler, 2008), in faster reading (Traxler & Tooley, 2008) and in picture-matching choices for ambiguous phrases (Branigan, Pickering, & McLean, 2005). In comprehension tasks, ERP studies revealed the attenuation of the P600 amplitude as a result of syntactic priming (Ledoux, Traxler, & Swaab, 2007;Tooley, Traxler, & Swaab, 2009).…”
Section: Introductionmentioning
confidence: 99%
“…Bock, 1986;Bock & Loebell, 1990) or in faster speech onsets for repeated syntactic structures (Corley & Scheepers, 2002;Segaert, Menenti, Weber, & Hagoort, 2011;Smith & Wheeldon, 2001;Wheeldon & Smith, 2003;Wheeldon, Smith, & Apperly, 2011). Syntactic priming in comprehension is shown in anticipatory eye-movements to pictures (Arai, van Gompel, & Scheepers, 2007;Carminati, van Gompel, Scheepers, & Arai, 2008;Thothathiri & Snedeker, 2008a;Traxler, 2008), in faster reading (Traxler & Tooley, 2008) and in picture-matching choices for ambiguous phrases (Branigan, Pickering, & McLean, 2005). In comprehension tasks, ERP studies revealed the attenuation of the P600 amplitude as a result of syntactic priming (Ledoux, Traxler, & Swaab, 2007;Tooley, Traxler, & Swaab, 2009).…”
Section: Introductionmentioning
confidence: 99%
“…The conditional probability p(structure|context story, Subject, Thothathiri and Snedeker (2008). The display contains two referents (horse and horn) whose labels share their onset ("hor…").…”
Section: Quantifying the Prediction Errormentioning
confidence: 99%
“…By reanalyzing data from a syntactic priming experiment (Thothathiri & Snedeker, 2008), we find that the error signal associated with a syntactic prime influences comprehenders' subsequent syntactic expectations. This follows directly from error-based implicit learning accounts of syntactic priming, but it is unexpected under accounts that consider syntactic priming a consequence of temporary increases in base-level activation.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations